Compound Fu brick tea modifies the intestinal microbiome composition in high‐fat diet‐induced obesity mice. Issue 10 (31st August 2020) - Zhou, Caibi; Zhou, Xiaolu; Wen, Zhirui; Liu, Liming; Yang, Zaibo; Yang, Lu; Li, Ping; Guo, Xiying; Mei, Xin
Abstract: Compound Fu Brick Tea (CFBT), which is from Duyun city in China, is a traditional Chinese dark tea, Fu Brick Tea, mixed with six herbal medicine. It is consumed by local people for reducing weight, but the mechanism is not clear. The disorder of intestinal microbiome caused by long‐term high‐fat diet (HFD) is one of the inducements of obesity and related metabolic syndrome. In this study, mice were fed with HFD to establish a high‐fat model. Fifty mice were randomly divided into six groups: normal control (CK), HFD model control (NK), positive control with medicine (YK), CFBT groups with low, middle, and high dose (FL, FM, FH). The V3‐V4 DNA region of fecal microbiome from mouse intestine was sequenced. The results showed that the diversity of intestinal microflora was highest in CK and lowest in NK. Compared with CK, the dominant bacterium Firmicutes was increased and Bacteroidetes decreased at phylum level in NK. Compared with NK, the abundance of microbiome in CFBT groups was significantly higher and the composition was changed: Muribaculaceae, Bacteroidaceae, and Prevotellaceae increased and Lachnospiraceae decreased in CFBT groups at family level, while at the genus level, Bacteroides increased and Lactobacillus decreased. These results conclude that CFBT can increase the abundance of intestinal microbiome in mice, promote the growth of beneficial bacteria and reduce the number of pathogenic bacteria, and restore the imbalance of intestinal microbiome caused by poor diet. Abstract : Compound Fu Brick Tea can increase the abundance of intestinal microbiome in mice, promote the growth of beneficial bacteria and reduce the number of pathogenic bacteria, and restore the imbalance of intestinal microbiome caused by high‐fat diet.